2018
DOI: 10.1139/cjc-2017-0407
|View full text |Cite
|
Sign up to set email alerts
|

Common bed bugs can biosynthesize pheromone components from amino acid precursors in human blood

Abstract: We have recently shown that the aggregation pheromone of the common bed bug, Cimex lectularius, comprises a six-component blend of dimethyl disulfide (DMDS), dimethyl trisulfide (DMTS), (E)-2-hexenal, (E)-2-octenal, 2-hexanone, and histamine. Here, we tested the hypothesis that bed bugs biosynthesize some pheromone components from amino acid precursors in human blood, namely DMDS and DMTS from L-methionine and histamine from histidine. We tested this hypothesis by (i) allowing bed bugs to feed on and metaboliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Such efforts include research that requires the laboratory breeding of thousands of animals not only for testing insecticides and critical temperatures (e.g. Ashbrook, Scharf, Bennett, & Gondhalekar, 2017, 2019; Gaire, Scharf, & Gondhalekar, 2019; Puckett, McDonald, & Gold, 2013; Romero, Potter, Potter, & Haynes, 2007), reviewed by Hase, 1930; Usinger, 1966; Feldlaufer, O'Connor, & Ulrich, 2018) but also for screening for novel control targets such as symbionts (Balvín, Roth, Talbot, & Reinhardt, 2018; Goodman, 2018), neuropeptides (Predel, Neupert, Derst, Reinhardt, & Wegener, 2018) or communication molecules (Gries, Zhai, Lewis, Britton, & Gries, 2018). All these targets are closely linked to the two major aspects that alter bedbug physiology, feeding and mating.…”
Section: Introductionmentioning
confidence: 99%
“…Such efforts include research that requires the laboratory breeding of thousands of animals not only for testing insecticides and critical temperatures (e.g. Ashbrook, Scharf, Bennett, & Gondhalekar, 2017, 2019; Gaire, Scharf, & Gondhalekar, 2019; Puckett, McDonald, & Gold, 2013; Romero, Potter, Potter, & Haynes, 2007), reviewed by Hase, 1930; Usinger, 1966; Feldlaufer, O'Connor, & Ulrich, 2018) but also for screening for novel control targets such as symbionts (Balvín, Roth, Talbot, & Reinhardt, 2018; Goodman, 2018), neuropeptides (Predel, Neupert, Derst, Reinhardt, & Wegener, 2018) or communication molecules (Gries, Zhai, Lewis, Britton, & Gries, 2018). All these targets are closely linked to the two major aspects that alter bedbug physiology, feeding and mating.…”
Section: Introductionmentioning
confidence: 99%
“…Histamine was recently identified as a close-range aggregation pheromone component in bed bug feces [ 24 ], with bed bugs likely synthesizing a majority of histamine de novo [ 25 ]. Histamine is a known food contaminant, mainly of fish and alcoholic beverages such as beer and wine [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bed bugs tend to cluster together in groups as a result of bed bug discharge of pheromones in their feces. Bed bugs release pheromones as soon as they identify safe shelters and a nearby food source, resulting in their occupation upon a surface as shown in hexenal, (E)-2-octenal, 2-hexanone, and less volatile histamine component [7,8]. Studies have shown that bed bugs biosynthesize some pheromone components such as DMDS, DMTS, and histamine from amino acid precursors in human blood, namely DMDS and DMTS from methionine and histamine from histidine [8].…”
Section: Histamine's Role As a Chemical Signature For Bed Bug Detectionmentioning
confidence: 99%
“…Bed bugs release pheromones as soon as they identify safe shelters and a nearby food source, resulting in their occupation upon a surface as shown in hexenal, (E)-2-octenal, 2-hexanone, and less volatile histamine component [7,8]. Studies have shown that bed bugs biosynthesize some pheromone components such as DMDS, DMTS, and histamine from amino acid precursors in human blood, namely DMDS and DMTS from methionine and histamine from histidine [8]. However, studies show that there are not enough precursors such as histidine in the blood to account for the high concentration of histamine that bed bugs excrete in their feces.…”
Section: Histamine's Role As a Chemical Signature For Bed Bug Detectionmentioning
confidence: 99%
See 1 more Smart Citation